2016
DOI: 10.3807/josk.2016.20.1.008
|View full text |Cite
|
Sign up to set email alerts
|

Ghost Imaging with Different Speckle Sizes of Thermal Light

et al.

Abstract: In this paper, we theoretically and experimentally analyze the impact of speckle size of pseudo-thermal light source on ghost imaging. A larger size of speckle can bring improvements in SNR and visibility. At the same time, the edge blur of the retrieved image will become more serious. We also present a setup which can mitigate the edge blur of larger speckle while maintaining the advantages of higher SNR and visibility by changing the speckle size of the object beam with a concave lens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Starting with object 1, the speckle size was increased from 36 µ m to 60 µ m in five steps, followed by reconstruction with 10,000 iterations under the same conditions. In the traditional single-size speckle pattern imaging condition, the retrieved ghost image CNRdependent speckle size was found to be in good agreement with [18][19][20][21][22][23], which indicates a growth of the CNR and a reduced resolution proportional to the speckle size in Figure 2 (black line with solid squares and black line with hollow squares). The highest CNR ghost image was obtained with the largest speckle size of 60 µ m. The best resolution was obtained with the smallest speckle size of 36 µ m.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Starting with object 1, the speckle size was increased from 36 µ m to 60 µ m in five steps, followed by reconstruction with 10,000 iterations under the same conditions. In the traditional single-size speckle pattern imaging condition, the retrieved ghost image CNRdependent speckle size was found to be in good agreement with [18][19][20][21][22][23], which indicates a growth of the CNR and a reduced resolution proportional to the speckle size in Figure 2 (black line with solid squares and black line with hollow squares). The highest CNR ghost image was obtained with the largest speckle size of 60 µ m. The best resolution was obtained with the smallest speckle size of 36 µ m.…”
Section: Resultsmentioning
confidence: 65%
“…At first, Bennink et al [4] presented an experimental demonstration of ghost imaging by using a pseudo-thermal light source. Recent studies [18][19][20][21][22] have shown that implementing a speckle-based imaging method is one of the strategies to improve the image quality in PGI. The ghost image quality, e.g., contrast-to-noise ratio (CNR) and resolution, highly depends on the characteristics of the speckle patterns.…”
Section: Introductionmentioning
confidence: 99%